THE EFFECT OF MAT JOYO APPLICATION ON STUDENTS’ UNDERSTANDING OF MATHEMATICAL CONCEPTS FIFTH GRADE ELEMENTARY SCHOOL - Ermawati, Diana; Amalia, Nova (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
AbstractThis research is based on the low ability of understanding mathematics in learning. Purpose of this study was to analyze differences in the ability to understand mathematical concepts before and after using the Mat Joyo application. Type of research is quantitative research with pre-experimental design research method with one group pretest-posttest design. Subjects in this study were all the fifth grade students at SD 1 Gemiring Kidul, 29 students. The data collection technique in this study was a test. The prerequisite test used the normality test with the Kolmogrov Smirnov test assisted by SPSS version 23. The hypothesis testing used the paired-samples t-test. Meanwhile, to find out the increase in students' understanding of mathematical concepts using the N-Gain test. The results showed that there were differences in the ability to understand mathematical concepts, these results were proven by results of the t-test of two dependent samples, namely sig <0.05 or 0.00 <0.05. Then there is an increase in the ability to understand mathematical concepts of 0.5922 in the medium category. It was concluded that the use of Mat Joyo application had an effect on ability to understand mathematical concepts of fifth grade students at SD 1 Gemiring Kidul.Keywords: Mat Joyo Application, Understanding of Mathematics  Concepts